Peningkatan Kapasitas Pegawai Melalui Program Rumah Sakit Aman Bencana (RSAB) di RSUD Kilisuci Kota Kediri - Ficky Adi Kurniawan; Anggoro Budi Prasetyo; Oktomi Wijaya; Nakhma’ Ussolikhah (Fakultas Teknik Universitas Maritim AMNI Semarang, 2025)
This research aims to see the results of activities to increase employee capacity through the disaster safe hospital (RSAB) program at Kilisuci Regional Hospital, Kediri City. Hospital preparedness plans are very important in ensuring the safety of the hospital environment and the actions that need to be taken to ensure health services remain available during a disaster situation. Kilisuci Regional Hospital does not yet have a preparedness plan that is documented, tested, and involves the surrounding community to be ready to face disasters. The methods used in this community empowerment activity include pretest-posttest, lecture-discussion, direct training/practice, observation and evaluation methods. The research results show that Disaster Management at the Kilisuci Regional Hospital is very necessary considering that Kediri City has a variety of potential disasters and is in an area that has potential threats from floods, fires, the Covid-19 pandemic, Mount Kelud eruptions, traffic accidents and earthquakes. There was an increase in pretest and posttest results of 14.60 points. It is felt that activities to strengthen employee capacity through the Hospital Disaster Plan (HDP) program need to be developed further because hospitals need more preparedness capacity in facing disasters or emergency situations and can support during hospital accreditation.